Adaptation of smart-object dimensions in the product design process to reduce household food waste - Muhammad Jameel, Mohamed Kamil; Chuah, Ee Hua; Mohd Najib, Abdullah Sani (University of Novi Sad, 2021)
Food waste is a huge problem across the world, but it's especially bad in developed countries such as Malaysia, according to the previous study. It is estimated that 1.3 billion tonnes of food are lost or wasted every year, ac- counting for one-third of all food produced for human consumption. Hence, the goal of this study is to supplement the solution within the framework of product design process based on the evaluation of food waste behaviour among household in Malaysia. As an approach for acquiring empirical data, a survey study was conducted with 52 respondents in Malaysia, including an analysis of similar existing products on the market, which was then followed by the design process. The findings suggest a multitude of design needs in preventing food waste behaviour among household in Malaysia, including the issues of the existing similar products on the market. Therefore, a few design criteria have been proposed and a set of semi-working food tracking models was successfully developed as a proposal for potential future devel- opment and production. It is hoped that the outcome of the study exhibits the synchronization of the product design process inside the smart-object dimensions in order to generate the design that helps to manage and reduce the amount of food waste created among household in Malaysia.